ANALISIS MANAJEMEN LAUNDRY DI RUMAH SAKIT UMUM DAERAH (RSUD) ARIFIN ACHMAD PROVINSI RIAU TAHUN 2019 - leni marlina; Dedi Afandi; Novita Rani (Al Tamimi Kesmas: Jurnal Ilmu Kesehatan Masyarakat (Journal of Public Health Sciences), 2019)
ABSTRACT Hospital laundry service is an important part of a hospital operation. Prelimenary survey conducted at Arifin Achmad General Hospital of Riau Province show thata lack of space.There are two sepate room washing room dan drying room and one room for ironing, pelipatan, distributing room. There are also too many broken laundry equipment. This study purposeis to analysis laundry management at Arifin Achmad General Hospital of Riau Province This study uses the deep interview, observation and document review methode with a qualitative approach and data validity of triangulation. There are six informant : laundry officer, Head of laundry, Head of medical instalation, Chief of monitoring and evaluation, Chief of Nurserry and vice director of medik and nursery at Arifin Achmad General Hospital of Riau Province . This studyresult show that there are many themes appear as the finding of the studyof laundry management. As for themes in the area of Human Resousches Quality. Less of training officer, less internal teknision, the provision of facilities and laundry equipmentProvision for supply of waterand the implemantation of the house in the form of disharging SOP, there are no wet for dirty linen, provision of identity not include the name of hospital, size an No, ID. There needs improvement to Laundry manajement become Sentral Linen conforming with established standart. Keywords : Laundry, Manajemen, Hospital Bibliography Literature : 40 (2004 - 2017)